2017
DOI: 10.1038/pr.2017.217
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for childhood interstitial lung disease among Japanese infants and children

Abstract: BackgroundGenetic variants responsible for childhood interstitial lung disease (chILD) have not been studied extensively in Japanese patients.MethodsThe study population consisted of 62 Japanese chILD patients. Twenty-one and four patients had pulmonary hypertension resistant to treatment (PH) and hypothyroidism, respectively. Analyses of genetic variants were performed in all 62 patients for SFTPC and ABCA3, in all 21 PH patients for FOXF1, and in a limited number of patients for NKX2.1.ResultsCausative genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
14
1
2
Order By: Relevance
“…However, reduced transcription of SFTPC due to promotor variant were associated with neonatal respiratory distress syndrome in late preterm infants (Wambach et al, 2010) and SP-C was absent in BALF samples of a family with chronic ILDs, together with reduced pro-SP-C staining, though no mutation was identified (Amin et al, 2001). While the majority of mutations leads to the onset of ILDs already in childhood (Chibbar et al, 2004;Hamvas et al, 2004;Tredano et al, 2004;Rosen and Waltz, 2005;Stevens et al, 2005;Bullard and Nogee, 2007;Guillot et al, 2009;Mechri et al, 2010;Citti et al, 2013;Henderson et al, 2013;Hepping et al, 2013;Turcu et al, 2013;Akimoto et al, 2014;Avital et al, 2014;van Hoorn et al, 2014;Kroner et al, 2015;Liptzin et al, 2015;Peca et al, 2015;Griese et al, 2016;Liu et al, 2016;Hayasaka et al, 2018) a subset of variants results in a manifestation in later childor adulthood (Lawson et al, 2004;Setoguchi et al, 2006;Markart et al, 2007;van Moorsel et al, 2010;Ono et al, 2011;Kuse et al, 2013) suggesting a chronic process.…”
Section: Sp-c Mutations In Human Patientsmentioning
confidence: 99%
“…However, reduced transcription of SFTPC due to promotor variant were associated with neonatal respiratory distress syndrome in late preterm infants (Wambach et al, 2010) and SP-C was absent in BALF samples of a family with chronic ILDs, together with reduced pro-SP-C staining, though no mutation was identified (Amin et al, 2001). While the majority of mutations leads to the onset of ILDs already in childhood (Chibbar et al, 2004;Hamvas et al, 2004;Tredano et al, 2004;Rosen and Waltz, 2005;Stevens et al, 2005;Bullard and Nogee, 2007;Guillot et al, 2009;Mechri et al, 2010;Citti et al, 2013;Henderson et al, 2013;Hepping et al, 2013;Turcu et al, 2013;Akimoto et al, 2014;Avital et al, 2014;van Hoorn et al, 2014;Kroner et al, 2015;Liptzin et al, 2015;Peca et al, 2015;Griese et al, 2016;Liu et al, 2016;Hayasaka et al, 2018) a subset of variants results in a manifestation in later childor adulthood (Lawson et al, 2004;Setoguchi et al, 2006;Markart et al, 2007;van Moorsel et al, 2010;Ono et al, 2011;Kuse et al, 2013) suggesting a chronic process.…”
Section: Sp-c Mutations In Human Patientsmentioning
confidence: 99%
“…Studies conducted in Asian countries indicated ABCA3 deficiency may indeed be rare, compared to SP‐C deficiency. A prospective cohort including neonatal patients conducted in Japan found that, of 62 chILD, 6 cases with SP‐C deficiency and none ABCA3 were identified . It is possible that the variants of genetic background may be responsible for the differences.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort including neonatal patients conducted in Japan found that, of 62 chILD, 6 cases with SP-C deficiency and none ABCA3 were identified. 18,19 It is possible that the variants of genetic background may be responsible for the differences. A population-based frequency of surfactant dysfunction mutations in a native Chinese cohort indicated that the collapsed carrier rate of deleterious ABCA3 mutations were 1.3%, significantly less than that of 3% to 5% reported previously in cohorts of European or African descent in the United States.…”
mentioning
confidence: 99%
“…Comparing the results of multiple studies shows that involvement of the recessive genes SFTPB and ABCA3 differs between populations [16,[35][36][37][114][115][116][117][118][119]. Furthermore, next to clinical differences between the studied cohorts, the background frequency of deleterious recessive alleles also differs between populations.…”
Section: Mutation Spectrummentioning
confidence: 99%